Editorial of International Journal of Pharmacy and Integrated Health Sciences - Prof. Dr. Abu Bakar Munir (Ph.D.) (International Journal of Pharmacy & Integrated Health Sciences, 2022)
It is a great pleasure to introduce this issue on emerging ideas in health services research, biological, pharmaceutical, integrated health sciences in the International Journal of Pharmacy & Integrated Health Sciences (IJPIHS). We editor encourage studies with rigorous methodology and contributions because this is essential to ensure that the conclusions drawn from the journal's publications are true and reliable. All articles provide interesting, novel and useful results covering different areas pharmaceutical chemistry, pharmaceutics, pharmacogenomics, pharmacology, natural product research, nanotechnology, bioinformatics, biotechnology, environmental sciences and genetic engineering. The newest studies dealing with biomedical applications are summarized in this issue of IJPIHS, with "new frontiers" playing a crucial role in this regard. Review articles and original research covering all facets of pharmaceutical and integrated health sciences, as well as cutting-edge protocols and techniques to assess healthcare professionals' knowledge, attitudes, and practices regarding various clinical issues, are among the contributions for this issue.